Unravelling the links between coach behaviour and coach-athlete relationships - Jowett, S.; Nicolas, M.; Yang, S. (European Journal of Sports & Exercise Science, 2017)
The study examined whether the quality of the coach-athlete relationship associates with a range of behaviours coaches manifest in training and competitions. The Coach Behaviour Scale for Sport (CBS-S) and the Coach-Athlete Relationship Questionnaire (CART-Q) measured coaching behaviours and relationships respectively. As neither of these scales was validated in French, the psychometric properties of both scales were examined indicating that they were psychometrically sound. Analysis revealed that athletes` perceptions of good quality relationships reflected in high levels of closeness and commitment were better and stronger predictors of a range of coach behaviours while high levels of complementarity only predicted positive personal rapport. Moreover, high levels of closeness (trust, respect, appreciation) predicted low levels of negative personal rapport. Overall, these results support the assumptions that good quality coach-athlete relationships supply the context within which athletes interact with their coaches. It is possible that athletes who develop strong connections with their coaches receive better coaching. Thus relationships may play a key role in developing effective coaching environments.